A Ketogenic Diet in Rodents Elicits Improved Mitochondrial Adaptations in Response to Resistance Exercise Training Compared to an Isocaloric Western Diet - Hyatt, Hayden W.; Kephart, Wesley C.; Holland, A. Maleah; Mumford, Petey; Mobley, C. Brooks; Lowery, Ryan P.; Roberts, Michael D.; Wilson, Jacob M.; Kavazis, Andreas N. (Frontiers in Physiology, 2016)
Purpose: Ketogenic diets (KD) can facilitate weight loss, but their effects on skeletal muscle remain equivocal. In this experiment we investigated the effects of two diets on skeletal muscle mitochondrial coupling, mitochondrial complex activity, markers of oxidative stress, and gene expression in sedentary and resistance exercised rats. Methods: Male Sprague-Dawley rats (9-10 weeks of age, 300-325 g) were fed isocaloric amounts of either a KD (17 g/day, 5.2 kcal/g, 20.2% protein, 10.3% CHO, 69.5% fat, n=16) or a Western diet (WD) (20 g/day, 4.5 kcal/g, 15.2% protein, 42.7% CHO, 42.0% fat, n=16) for 6 weeks. During these six weeks animals were either sedentary (SED, n=8 per diet group) or voluntarily exercised using resistance-loaded running wheels (EXE, n=8 per diet group). Gastrocnemius was excised and used for mitochondrial isolation and biochemical analyses. RESULTS: In the presence of a complex II substrate, the respiratory control ratio (RCR) of isolated gastrocnemius mitochondria was higher (p<0.05) in animals fed the KD compared to animals fed the WD. Complex I and IV enzyme activity was higher (p<0.05) in EXE animals regardless of diet. SOD2 protein levels and GLUT4 and PGC1α mRNA expression were higher (p<0.05) in EXE animals regardless of diet. CONCLUSION: Our data indicate that skeletal muscle mitochondrial coupling of complex II substrates is more efficient in chronically resistance trained rodents fed a KD. These findings may provide merit for further investigation, perhaps on humans.